Investigation of the parametric vibration of the orthotropic plates subjected to periodic in plane forces by multi-modal approximation and R-functions method - Awrejcewicz, Jan; Kurpa, Lidiya; Mazur, Olga (NTU "KhPI", 2010)
The original method of studying parametric vibrations of orthotropic plate with complex shape is proposed. Suggested approach is based on combined application of variational methods and the R-functions theory. Using the proposed method and developed software the regular and chaotic regimes of T-shaped plate are analyzed.